Preparation of the New Military Units for the Front (the Experience of the Siberian Military District) - A. G. Bayer (MGIMO University Press, 2015)
By the beginning of the Great Patriotic War, the Soviet armed forces were no match in overall power terms to the fully mobilized Wehrmacht, but in terms of the number of major weapons they surpassed it. By the summer of 1941, they totaled 5.7 million people. Ground troops of the Red Army included 303 Division 3 separate rifle and 16 airborne brigades. However, all of them, except the cavalry, were in the process of reorganization and formation and were unprepared to repel aggression. Incompleteness of reforms and a number of other reasons, led from the first days of the war to serious losses in the ranks of the Red Army. To make up for the losses it was required to mobilize significant resources, a substantial part of which has been lost in the abandonment of the western Soviet territories. The situation at the front in the first month of military operations required to supply the army with new compounds. In view of the fact that the mobilization plan did not provide for the formation of new compounds, it had to solve the problem from scratch. In addition to organizing training it had to urgently address the issue of creation of new military units. The task has been assigned primarily to internal military districts, including the Siberian Military District. In general, during the Great Patriotic War in the Siberian Military District 4 tactical formations, 43 infantry and 6 cavalry divisions, 30 infantry, mortar and ski teams were formed. Many of them have distinguished themselves in battle and have been awarded orders and honorary titles Guard names.